Table 2_Differential gene expression in ripe mango fruit (Mangifera indica L. cv. Azúcar) that favors the pathogenicity of the endophyte Colletotrichum tropicale.xlsx - Andrés F. Quintero-Mercado (22569440) (2025)
Colletotrichum tropicale is an endophyte that has been reported as a pathogen in ripe mango fruits (Mangifera indica L. cv. Azúcar) in Magdalena, Colombia, causing anthracnose. However, gene expression in the host that promotes its lifestyle transition remains unknown. This study aimed to analyze gene expression during the interaction between ripe mango fruit cv. Azúcar and C. tropicale to identify differentially expressed host genes that facilitate the pathogen’s infection process. RNA sequencing (RNA-seq) analysis was conducted at 0 and 12 h post inoculation (hpi), including de novo assembly and bioinformatic functional annotation using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). A total of 5,435 differentially expressed genes (DEGs) were identified in the interaction, of which only 421 DEGs were detected in ripe mango fruits. Among these, 379 were upregulated and 42 were downregulated (T0 vs. T12 hpi). GO functional annotation of downregulated fruit genes revealed that the molecular functions affected at 12 hpi were related to the plant’s defensive oxidative burst mediated by reactive oxygen species (ROS)—including NADPH oxidase activity, hydrogen peroxide formation, and the action of peroxidases and oxidoreductase enzymes—whereas upregulated genes were associated with stress response, defense, transferase activity, and kinase activity. KEGG analysis identified pathways related to mitogen-activated protein kinase (MAPK) signaling, pathogen-associated molecular pattern (PAMP)-triggered immunity, and phenylalanine metabolism. In conclusion, ripe mango fruit cv. Azúcar activates a defense response against C. tropicale at 12 hpi that does not overcome the pathogen’s initial quiescent phase but instead facilitates conditions for its establishment by suppressing oxidative burst pathways, which may later contribute to oxidative stress during the necrotrophic phase.